Balancing democracy: Majoritarianism vs. expression of preference intensity - Asaf D. M. Nitzan; Shmuel Nitsan (Bar-Ilan University, Department of Economics, 2023)
Direct confrontation between majority rule (MR) and the most in-depth studied scoring rules - the Borda rule (BR) and the plurality rule (PR) - on the basis of their fundamental weaknesses (violating one of the two principles: majoritarianism and suitable recognition of preference intensity) has not been attempted. Defining the cost of a rule as the expected erosion of the principle that it violates, this study fills the gap by comparing MR with PR and BR in terms of their mutual costs. The main findings are the evident superiority of PR over MR and the superiority of MR over BR.
Keywords: 330